PID Control and Input Shaping for Quadrotor UAV Stabilization and Payload Swing Reduction - Ramli, Liyana; Mat Lazim, Noor Hanis Izzuddin; Mohd Awi, Amalin Aisya; Mohd Shukor, Aina Syazwin (Applications of Modelling and Simulation, 2025)
Controlling an under-actuated quadrotor system with a suspended payload poses significant challenges due to payload–attitude coupling, where excessive payload swing can adversely affect the quadrotor’s stability and performance. This study proposes an optimal Unity Magnitude Zero Vibration (UMZV) input shaper to minimize payload swing, combined with a feedback control strategy for managing the quadrotor’s position and attitude. To enhance swing suppression, the input shaper parameters are optimized using the Particle Swarm Optimization (PSO) algorithm. In addition, a PID controller is employed to regulate the quadrotor’s motion, ensuring effective swing suppression while maintaining desirable attitude and position control. Simulation results demonstrate that the proposed control scheme achieves a substantial reduction in payload swing of at least 65.28% compared to existing methods. Furthermore, it delivers improved attitude and position tracking performance, confirming its effectiveness in managing the coupled dynamics of the quadrotor–payload system.